Examination of wheat rheological characteristics by near-infrared spectroscopy - Kónya, Éva; Győri, Zoltán (Acta Agraria Debreceniensis, 2012)
Near-infrared spectroscopy has many advantages that make it a widely used analitical method in the different areas, like agricultural and food industry as well. In wheat quality control rheological characteristics of dough made from wheat flour are as important as physical and chemical properties too. In this work we examined rheological properties of wheat flour samples by alveograph, and spectral data of the same samples were collected by FOSS Infratec 1241 instrument. Modified partial least squares analyses on NIR spectra were developed for two alveograph parameter (P/L és W) to get calibration equations.